2015
DOI: 10.2340/00015555-1974
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin Mutations with Palmoplantar Keratoderma, Woolly Hair and Cardiomyopathy

Abstract: Mutations in genes encoding for desmosomal components are associated with a broad spectrum of phenotypes comprising skin and hair abnormalities and account for 45-50% of cases of arrhythmogenic right ventricular cardiomyopathy. Today, more than 120 dominant and recessive desmoplakin (DSP) gene mutations have been reported to be associated with skin, hair and/or heart defects. Here we report on 3 cases with yet unreported DSP mutations, c.7566_7567delAAinsC, p.R2522Sfs*39, c.7756C>T, p.R2586*, c.2131_2132delAG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
1
40
0
3
Order By: Relevance
“…Src inhibition prevented phosphorylation of plakophilin-3, which reduced the disruptive effects of Pemphigus Vulgaris autoimmune antibodies (Cirillo et al 2014). Genetic loss of desmoplakin causes the loss of skin integrity due to intercellular separation and loss of desmosomal linkages to the cytokeratin intermediate filaments (Vasioukhin et al 2001b), and desmoplakin mutations have been found in cases of palmoplantar keratoderma, woolly hair syndrome, and cardiomyopathy (Pigors et al 2015). Desmoplakin is phosphorylated in the presence of Pemphigus Vulgaris autoimmune antibodies, which decreases cytokeratin intermediate filament binding to desmosomes (Fig.…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…Src inhibition prevented phosphorylation of plakophilin-3, which reduced the disruptive effects of Pemphigus Vulgaris autoimmune antibodies (Cirillo et al 2014). Genetic loss of desmoplakin causes the loss of skin integrity due to intercellular separation and loss of desmosomal linkages to the cytokeratin intermediate filaments (Vasioukhin et al 2001b), and desmoplakin mutations have been found in cases of palmoplantar keratoderma, woolly hair syndrome, and cardiomyopathy (Pigors et al 2015). Desmoplakin is phosphorylated in the presence of Pemphigus Vulgaris autoimmune antibodies, which decreases cytokeratin intermediate filament binding to desmosomes (Fig.…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…Both Carvajal disease (caused by DSP mutations) and Naxos disease (caused by plakoglobin mutations) characteristically present with a triad of ‘woolly’ hair, markedly thickened skin of the palms and soles (palmoplantar keratoderma) from infancy, and later, development of severe cardiomyopathy in childhood . Although rare autosomal dominant cardiocutaneous cases have been reported, there was confusion regarding whether both the skin and the heart would be affected in heterozygous loss‐of‐function (nonsense or frameshift) mutation carriers, which was often attributed to observational bias in these families as either purely cardiac examinations or only dermatological examinations were carried out. On this basis, we have performed the first systematic analysis of a cohort of patients.…”
mentioning
confidence: 99%
“…Particularly noteworthy is that SLINGER was able to yield associations for coronary artery disease, a condition where no association was reported in PrediXcan3. Specifically, we find significant association for desmoplakin (DSP), which has been robustly implicated in other cardiovascular diseases, such as heart failure10, epicardial ventricular tachycardia11 and cardiomyopathy12. A complete list of gene-disease associations is included in Supplementary Table 3.…”
Section: Discussionmentioning
confidence: 87%